(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background:Staphylococci are a group of bacteria that cause diseases ranging from minor skin infections to life-threatening bacteremia. Biofilm formation was determined by a number of methods and is available to detect the capability of staphylococci to colonize the biomedical devices. The icaA and icaD have been reported to play a significant role in biofilm formation. Objective:To achieve and detect the molecular basis of adhesion properties in respect to methicillin resistant Staphylococcus aureus. Methods:Clinical samples were taken from Burn patients; identified and Methicillin susceptibility was tested. The genes icaA and icaD were amplified in methicillin resistant Staphylococcus aureus and the polymerase chain reaction products were sequenced and aligned with the previous recorded sequences online. Results:There was a great correlation between the presence of icaD genes and the slime production. Methicillin resistant Staphylococcus aureus did not reveal any correlation between icaA and icaD and slime layer production; nonetheless, a correlation was noticed between icaD alone and a biofilm production Conclusion:The present findings indicated that methicillin resistant Staphylococcus aureus was able to form biofilm. None of the methicillin resistant Staphylococcus aureus isolates harboured icaA; while 100% of them contained icaD. Keywords:Methicillin resistant Staphylococcus aureus, icaA, icaD gene Citation:Mohamad DA. Molecular study of biofilm production by methicillin resistant Staphylococcus aureus. Iraqi JMS. 2019; 17(3&4): 191-200. doi: 10.22578/IJMS.17.3&4.5